Adverse effects of patent pooling on product development and commercialization - Thomas D. Jeitschko; Nanyun Zhang (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2013)
The conventional wisdom is that the formation of patent pools is welfare enhancing when patents are complementary, since the pool avoids a double-marginalization problem associated with independent licensing. This conventional wisdom relies on the effects that pooling has on downstream prices. However, it does not account for the potentially significant role of the effect of pooling on downstream innovation. The focus of this paper is on downstream product development and commercialization on the basis of perfectly complementary patents. We consider development technologies that entail spillovers between rivals, and assume that final demand products are imperfect substitutes. When pool formation facilitates information sharing and either increases spillovers in development or decreases the degree of product differentiation, patent pools can adversely affect welfare by reducing the incentives towards product development and product market competition|even with perfectly complementary patents. The analysis modifies and even negates the conventional wisdom for some settings and suggests why patent pools are uncommon in science-based industries such as biotech and pharmaceuticals that are characterized by tacit knowledge and incomplete patents.
Keywords: O3; L1; L2; L4; L6; 330; Patent Pools; Research and Development; Innovation; Tacit Knowledge; BioTechnology; Pharmaceutical